Orthogonal design-based investigation of dose, time point, and treatment course on the toxicity-efficacy transition of triptolide in collagen-induced arthritis mice - Shuai Huang; Lu Xu; Yunzhe Wu; Kai Chen; Nan Sun; Zhe Feng (Frontiers in Pharmacology)
In recent years, the potential application of Tripterygium wilfordii Hook f. (TWHF) in the treatment of rheumatoid arthritis (RA) has garnered increasing attention in both academic research and clinical practice. However, the effective use of rheumatoid arthritis is limited in clinical practice by its severe toxic side effects. We conducted a comprehensive analysis of the effects of triptolide dose, treatment course, and time point on the clinical efficacy and safety of treating experimental arthritis. This work employed an orthogonal design grouping and three-factor, three-level dose, treatment course, and time point modeling of collagen-induced arthritis (CIA) in female C57BL/6 mice. Using smears from exfoliated mouse vaginal cells, the estrous cycle was observed. Mice blood was tested by the enzyme linked immunosorbent assay (ELISA) for ovarian hormones such as estradiol (E2) and follicle stimulating hormone (FSH), as well as inflammatory markers such as interleukin-6 (IL-6) and interleukin-17A (IL-17A). In CIA mice, triptolide changed serum E2 and FSH levels, the estrous cycle, arthritis scores, IL-6, and IL-17A levels. The inhibitory effect of triptolide on IL-17A was significantly influenced by the time point of administration. For triptolide therapy of CIA mice, a high benefit-low risk dosage schedule is 150 μg/kg/d −23:00–6 weeks. Therefore, in clinical applications, optimizing the TWHF dosing regimen (including dose, time point, and treatment course) may help to minimize ovarian toxicity while retaining therapeutic efficacy.